2016
DOI: 10.5194/tc-10-2415-2016
|View full text |Cite
|
Sign up to set email alerts
|

Three-year monitoring of stable isotopes of precipitation at Concordia Station, East Antarctica

Abstract: Abstract. Past temperature reconstructions from Antarctic ice cores require a good quantification and understanding of the relationship between snow isotopic composition and 2 m air or inversion (condensation) temperature. Here, we focus on the French–Italian Concordia Station, central East Antarctic plateau, where the European Project for Ice Coring in Antarctica (EPICA) Dome C ice cores were drilled. We provide a multi-year record of daily precipitation types identified from crystal morphologies, daily preci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(133 citation statements)
references
References 50 publications
5
110
1
Order By: Relevance
“…2, hoarfrost mainly occurs in winter, at deep temperatures when absolute humidity is comparatively low. While 130 days with hoarfrost have temperatures between −60 and −70 • C, about 70 hoarfrost days are in the temperature range −60 to −50 • C; only less than 30 days show temperatures higher than −50 • C. This means that hoarfrost does not have a specific fingerprint due to its crystal type and formation process, as stated in a preliminary study by Stenni et al (2016), but, as speculated about qualitatively by Stenni et al (2016) already, the different signal is due to the low temperatures prevailing at days with hoarfrost formation.…”
Section: Mcimmentioning
confidence: 68%
See 4 more Smart Citations
“…2, hoarfrost mainly occurs in winter, at deep temperatures when absolute humidity is comparatively low. While 130 days with hoarfrost have temperatures between −60 and −70 • C, about 70 hoarfrost days are in the temperature range −60 to −50 • C; only less than 30 days show temperatures higher than −50 • C. This means that hoarfrost does not have a specific fingerprint due to its crystal type and formation process, as stated in a preliminary study by Stenni et al (2016), but, as speculated about qualitatively by Stenni et al (2016) already, the different signal is due to the low temperatures prevailing at days with hoarfrost formation.…”
Section: Mcimmentioning
confidence: 68%
“…Hoarfrost exhibited significantly lower δ 18 O and δD values and higher deuterium excess than snowfall and diamond dust. Whereas Stenni et al (2016) state that hoarfrost has a distinct fingerprint among the various precipitation types, implying that moisture sources and or the hydrological cycle might be different for hoarfrost, our current, more detailed study has shown that this "fingerprint" is due to the fact that hoarfrost occurs predominantly during the cold period. Relatively large amounts of hoarfrost are measured after synoptic snowfall events, when humidity is still increased after moisture transport from lower latitudes, implying that hoarfrost basically has the same moisture sources as the other precipitation types.…”
Section: Comparison Of Dome C and Dome Fujimentioning
confidence: 83%
See 3 more Smart Citations